STUDENT-CENTERED LEARNING IN ENGLISH LANGUAGE CLASSROOMS: ENGAGEMENT AND ACHIEVEMENT (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
In modern English language teaching (ELT), the shift from teacher-led lectures to student-driven discovery has transformed how students acquire language. This study examines how student-centered learning (SCL) influences student engagement and academic outcomes. By treating students as active partners rather than passive recipients, the approach fosters autonomy and meaningful communication. Results suggest that SCL significantly boosts intrinsic motivation and language retention, though it requires teachers to adopt new roles as facilitators.